Unearthing the Liturgy"s true meaning to counter church secularisation: Father Alexander Schmemann - Streza, Ciprian Ioan (HTS teologiese studies, 2023)
Secularism is a very popular topic in social sciences and in theology. Father Alexander Dmitrievich Schmemann (1921–1983) addressed this topic and raised many questions, which are still very relevant in today’s Eastern European context. He presented the distinctive vision of the Eastern Church, according to which all the solutions to overcome the actual crisis caused by secularism can be found by rediscovering the Liturgy of the Church as the primary source not only for theology but for all other aspects of church life.Contribution: The present article aims to discuss the whole problematisation related to the impact of secularism on orthodoxy and to present the highly topical solutions that Father Alexander Schmemann proposed for the survival of the Christian Orthodox ethos in the novel conditions of the postmodern world.